Proses Komunikasi Organisasi dalam Koordinasi Pelaksanaan Operasi Pencarian dan Pertolongan oleh Kantor Search And Rescue Medan - Sariman Sutrisno Sitorus; Yan Hendra; Bahrum Jamil (Universitas Medan Area, 2017)
Communication process is a process that describes the inter-human communication activities that are interactive, relational, and transactional where communicators send messages to the communicant through a certain media with a specific purpose and purpose. The operation of SAR is related to saving human life when disaster occurs. Organizational communication and coordination seen in SAR operations handling sinking case of KM. Kumala Endah where the distance of the location of the event far enough from the SAR Medan office, while the communication must continue to run during the SAR operation process takes place. This research uses qualitative approach with descriptive data analysis method. This approach was chosen because the researchers wanted to obtain how the process of organizational communication in coordinating the implementation of SAR operations conducted SAR Medan office. Data collection techniques used interviews, observation and documentation studies. The results showed that organizational communication and coordination conducted by the head of Medan SAR office and rescuer team SAR Medan office during the operation handling case sinking of KM. Kumala Endah has gone well. Constraints faced by SAR team when handling KM.Kumala Endah sinking case is a big wave problem, dirty sea water that reduces the divers's visibility when dive searching for victims and disruption of reception signal via HT (HandyTalk) but everything can be overcome well.